Di‐Iron(II) [2+2] Helicates of Bis‐(Dipyrazolylpyridine) Ligands: The Influence of the Ligand Linker Group on Spin State Properties. Issue 9 (27th December 2022) - Kulmaczewski, Rafal; Armstrong, Isaac T.; Catchpole, Pip; Ratcliffe, Emily S. J.; Vasili, Hari Babu; Warriner, Stuart L.; Cespedes, Oscar; Halcrow, Malcolm A.
Abstract: Four bis[2‐pyrazol‐1‐yl‐6‐pyrazol‐3‐ylpyridine] ligands have been synthesized, with butane‐1, 4‐diyl ( L 1 ), pyrid‐2, 6‐diyl ( L 2 ), benzene‐1, 2‐dimethylenyl ( L 3 ) and propane‐1, 3‐diyl ( L 4 ) linkers between the tridentate metal‐binding domains. L 1 and L 2 form [Fe2 (μ− L )2 ]X4 (X − =BF4 − or ClO4 − ) helicate complexes when treated with the appropriate iron(II) precursor. Solvate crystals of [Fe2 (μ− L 1 )2 ][BF4 ]4 exhibit three different helicate conformations, which differ in the torsions of their butanediyl linker groups. The solvates exhibit gradual thermal spin‐crossover, with examples of stepwise switching and partial spin‐crossover to a low‐temperature mixed‐spin form. Salts of [Fe2 (μ− L 2 )2 ] 4+ are high‐spin, which reflects their highly twisted iron coordination geometry. The composition and dynamics of assembly structures formed by iron(II) with L 1 − L 3 vary with the ligand linker group, by mass spectrometry and 1 H NMR spectroscopy. Gas‐phase DFT calculations imply the butanediyl linker conformation in [Fe2 (μ− L 1 )2 ] 4+ influences its spin state properties, but show anomalies attributed to intramolecular electrostatic repulsion between the iron atoms. Abstract : This diiron(II) complex has been crystallized in three different helicate conformations, which differ in the torsions of the butane‐1, 4‐diyl ligand linker groups. The crystals exhibit a range of spin state properties, including stepwise spin‐crossover of the two iron atoms. A related ligand with a rigid pyrid‐2, 6‐diyl spacer forms more a distorted, high‐spin diiron(II) helicate structure.